Notes to Philosophy 167: Class 5 -- Other Developments in Astronomy from 1609 to 1642 -- Part 4. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Galileo's Contributions to Astronomy, 1609-1633:Sidereus Nuncius -- The First Telescopic Results (1610); Generally corresponds to the video segment: Class 5, Part 4.